ANALISIS KATA AMR DALAM ALQURAN SURAH AL-ALAQ AYAT 1-5 : STUDI PERINTAH DAN KEHENDAK ALLAH - Hadichintya, Nesya; Harahap, Indah Salsabila (Yayasan Pendidikan Tanggui Baimbaian, 2024)
The purpose of this writing is to analyze the word amr in Surah Al-Alaq verses 1 and 3, and the method was taken to analyze this journal is a qualitative approach method with a library research method.The word insya’ is divided into two categories: insya’ thalabi and insya’ ghairu thalabi. Insya’ thalabi, which includes amr, is a word that desires the realization of a demand. In this context, amr etymologically means an order and in terminology in the science of balagah refers to the demand for the implementation of a job from a higher party to a lower party. In addition, the meaning of amr can vary, including obligations, recommendations, guidance, prayers, requests, and others, depending on the context of its use. A special analysis of the letter Al-Alaq verses 1 and 3 shows the importance of the command to read as a symbol of the beginning of knowledge and grace of Allah. This command, delivered by the Angel Gabriel, underlines the significance of reading by mentioning the name of God as the key to understanding creation and achieving glory from Him. The repetition of this command emphasizes the purpose and benefits of reading in human life. And the findings obtained in this journal because no one discussed this title in previous findings and in my opinion, this surah al-Alaq is the first surah that was revealed and it shows a command sentence according to the title of this journal.